A CRISPR approach to manipulating NK cell receptor ligand expression - Kristensson, Linnea (My University, 2018)
Natural killer (NK) cells are important innate lymphocytes in the immune system and have been considered to be vital in fighting cancer, virus infections as well as regulating immune responses. The activity of NK cells is regulated via a complex signaling between inhibitory and activating receptors. Ligands for most of the ac-tivating receptors have been discovered but no endogenous ligand for one of the important natural cytotoxicity receptors, NKp46 has been identified. Therefore, the long term aim of this thesis project was to define ligand candidates for the acti-vating receptor NKp46 with intermediate aims to manipulate expression of NK cell activating receptor ligands in the K562 cell line using a CRISPR approach. The result from the performed cytotoxicity assays demonstrated the importance of the activating receptors NKp30 and DNAM-1 in elimination of K562 cells and the expression of the complementary ligands NCR3LG1, PVR and NECTIN2 was confirmed using RT-qPCR. The successful creation of a Cas9-expressing K562 cell line was demonstrated, including verification of Cas9 protein expression using both flow cytometry and western blot. Following that, a constructed plasmid with the gRNA for the B7-H6 gene, NCR3LG1, was generated and shown to create a cleavage and mutation within the gene. The engineered cell line was ultimately shown to have a reduced expression of the B7-H6 protein, indicating the successful knockout of the NCR3LG1 gene.
Keywords: Livsvetenskaper; Cellbiologi; Cell- och molekylärbiologi; Immunologi inom det medicinska området; Life Science; Cell Biology; Cell and Molecular Biology; Immunology in the medical area